Matching and Winning? The Impact of Upper and Middle Managers on Firm Performance in Major League Baseball - Peeters, Thomas L. P. R.; Salaga, Steven; Juravich, Matthew (Management Science, 2020)
We investigate the joint impact of managers at different hierarchical levels on firm performance in Major League Baseball. We separately quantify the contribution of upper and middle managers and the impact of their match quality—the degree to which managers cooperate effectively across layers to impact firm success. We establish that match quality is a statistically significant and economically meaningful driver of firm performance. Higher-quality managers tend to be matched together across levels and achieve higher match quality during their joint employment. Match quality does not improve over the length of a joint employment spell, but lower match quality is found in pairs with more divergent educational attainment and prior strategic approaches. Hence, match quality is partly innate, and manager pairings may have difficulty improving their cooperation through learning. When we control for match quality, we find significantly lower estimates of heterogeneity in manager ability compared with commonly used estimators of managerial impact. Still, both middle and upper managers retain a meaningful impact on firm performance. This paper was accepted by Bruno Cassiman, business strategy.